Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.

Concise approach for central core of trigolutes: total synthesis of trigolute B and 3-epi-trigolute B and analogues - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Tetrahedron, 2017)
A concise approach comprising a combination of the Pd- or Ir-catalyzed Tsuji-Trost allylation and olefin dihydrox-ylation/acid catalyzed lactonization has been developed to construct the central spirolactone core of trigolutes with the requisite functional groups. A large number of analogues of trigolute B have been synthesized. Furthermore, the synthesis of both (±)-trigolute B and (±)-3-epi-trigolute B has been accomplished in 4–5 steps from easily accessible building blocks.

Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis